Association between selected single nucleotide polymorphisms (SNPS) in chromosome 5 and anti-malaria antibodies in a malaria endemic area in southern Sri Lanka - Dewasurendra, R.L.; Suriyaphol, P.; Fernando, S.D.; Carter, R.; Karunaweera, N.D. (My University, 2012)
Malaria incidence, at present, is low in Sri Lanka and the cases reported from Moneragala District, which was a malaria endemic area, have reduced; but a study of host factors associated with protection is important to achieve targets for malaria elimination. This study planned to investigate the antibody profile of some specific anti malarial antibodies and study its association with host genetic mutations in chromosome 5.